Fragmentation of thin plates by dot impact - Brodskii, R.Ye.; Kulik, T.V. (Functional Materials, 2015)
In this paper we study the case of two-dimensional single-impact fragmentation, namely the fragmentation of the circular thin plate by dot impact. The distribution density of the fragments by mass was obtained analytically in the case of the central strike and numerically for arbitrary random point of impact. The study was conducted for different values of the number of fissures, the dependence of the distribution parameters on that number was obtained.